Development of Parenting Models in Improving Children's Moral Development - Widya Masitah; Juli Maini Sitepu (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2021)
The goal of the study was to find a good parenting model to improve moral development in children. In addition, it is expected that after this parenting model is applied by parents it can help reduce immoral behavior. This research is a model study where data collection techniques are carried out by distributing questionnaires to parents of children from 6-10 years of age who attend SDIT in the city of Medan. The population in the study was 3,904 and the sample numbered 350. From the results obtained in this study, the parenting model that is best used to develop child morale is authoritarian parenting where this parenting balances clear and high expectations with emotional support and recognition of children's autonomy. Authoritative parents try to direct the child, but in a rational way.